An updated synthesis of N1′‐([11C]methyl)naltrindole for positron emission tomography imaging of the delta opioid receptor. (15th December 2020) - Kaur, Tanpreet; Brooks, Allen F.; Hockley, Brian G.; Torres, Jovany; Henderson, Bradford D.; Scott, Peter J.H.; Shao, Xia
Abstract : A new method for the synthesis of the highly selective delta opioid receptor (DOR) antagonist radiotracer N1 ′‐([ 11 C]methyl)naltrindole ([ 11 C]MeNTI) is described. The original synthesis required hydrogenation of a benzyl protecting group after 11 C‐labeling, which is challenging in modern radiochemistry laboratories that tend to be heavily automated and operate according to current good manufacturing practice. To address this challenge, we describe development of a novel MeNTI precursor bearing a methoxymethyl acetal (MOM) protecting group, which is easily removed with HCl, and employ it in an updated synthesis of [ 11 C]MeNTI. The new synthesis is fully automated and validated for clinical use. The total synthesis time is 45 min and provides [ 11 C]MeNTI in good activity yield (49 ± 8 mCi), molar activity (3, 926 ± 326 Ci/mmol) and radiochemical purity (97% ± 2%). Abstract :